The occupational health and safety evaluation of official veterinarians in turkey - Gökhan Aslım; Aşkın Yaşar (Eurasian Journal of Veterinary Sciences)
Aim: The study aims to reveal the risks that veterinarians who work in the Ministry of Agriculture and Forestry in Turkey faced and/or may face in terms of occupational health safety and to develop a questionnaire regarding the issue. Materials and Methods: The population of the study was made up of veterinarians serving in the Ministry of Agriculture and Forestry. The provinces from which the representative samples will be taken were determined by taking into consideration the presence of Ministry affiliated institutions and the potential of participating groups that are included in the sample to be present, based on Turkey's geographical regions. A total of 630 official veterinarians participated in the survey. The obtained data were analysed using SPSS 25 Statistical Program. Results: The study determined the situations that the participants may face the most in terms of occupational health safety as accident risk, contagious disease and skin diseases while the situations to be faced the least were heavy load, frazzle, damaging the equipment or products and being exposed to physical violence. Conclusion: An important condition of providing quality veterinarian service for public and animal health is healthy veterinarians and this may possibly be provided with a working environment where the elements of occupational health and safety are adequate. It may be asserted that the provision of this environment is one of the preliminary and important duties of the Ministry and to this end, employees' occupational health safety must be planned and all types of measures must be taken.